2021
DOI: 10.12775/setf.2021.017
|View full text |Cite
|
Sign up to set email alerts
|

A Tale of Two Perspectives: How Psychology and Neuroscience Contribute to Understanding Personhood

Abstract: Empirical science, such as psychology and neuroscience, employ diverse methods to develop data driven models and explanations for complex phenomena. In research on the self, differences in these methods produce different depictions of persons. Research in developmental psychology highlights the role of intuitive beliefs, such as psychological essentialism and intuitive dualism, in individuals’ singular, cohesive, and stable sense of self. On the other hand, research in neuroscience highlights the de-centralize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Furthermore, the religious and spiritual background of the studied population could have also resulted in these inconsistent findings, as multiple studies have shown the helpful role of spiritual and religious capital in coping with and protecting against COVID-19 psychological and mental stress [51,52]. Personality traits also play an important role in COVID-19-related changes and impacts where agreeable, extraverted, and conscientious persons had few COVID-19 related impacts compared to neurotic persons, who could be easily harmed [53][54][55].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the religious and spiritual background of the studied population could have also resulted in these inconsistent findings, as multiple studies have shown the helpful role of spiritual and religious capital in coping with and protecting against COVID-19 psychological and mental stress [51,52]. Personality traits also play an important role in COVID-19-related changes and impacts where agreeable, extraverted, and conscientious persons had few COVID-19 related impacts compared to neurotic persons, who could be easily harmed [53][54][55].…”
Section: Discussionmentioning
confidence: 99%
“…Relative to the neurosciences, psychology is much better placed as a scientific counterpart in a comprehensive study of the human person (Smith 2021). First, psychology deals with thoughts, beliefs and behavior without further justification; that is just its field.…”
Section: The Methodological and Theoretical Richness Of Psychological Sciencementioning
confidence: 99%